Paradoxia Epidemica : The Renaissance Tradition of Paradox - Colie, Rosalie Littell (Book collections on Project MUSE., 2015)
Paradoxia Epidemica is a broad-ranging critical study of Renaissance thought, showing how the greatest writers of the period from Erasmus and Rabelais to Donne, Milton, and Shakespeare made conscious use of paradox not only as a figure of speech but as a mode of thought, a way of perceiving the universe, God, nature, and man himself. The book consists of an introduction (historical and topological) and sixteen chapters grouped according to broad types of paradox: rhetorical, theological, ontological, epistemological. Within this framework the author interprets individual writings or art forms as parts of a rich tradition. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.